ROMANTICISM AS SOCIO-CULTURAL PHENOMENON - Yulian Evgenievich Grinivetskiy (Вестник Северо-Кавказского федерального университета, 2022)
The article dwells on Romanticism viewed as a socio-cultural phenomenon. There has been an investigation into various socio-cultural phenomena from the stance of Romanticism with certain generalizations made.